2019
DOI: 10.3389/fnins.2019.00476
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Modifications in Alzheimer’s Neuropathology and Therapeutics

Abstract: Transcriptional activation is a highly synchronized process in eukaryotes that requires a series of cis - and trans -acting elements at promoter regions. Epigenetic modifications, such as chromatin remodeling, histone acetylation/deacetylation, and methylation, have frequently been studied with regard to transcriptional regulation/dysregulation. Recently however, it has been determined that implications in epigenetic modification seem to expand into various neurode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 126 publications
0
46
0
2
Order By: Relevance
“…Results reported by Dr. Cahill at the symposium have since been published (Thejer, Adhikary, Kaur, et al, 2020;Thejer, Adhikary, Teakel, et al, 2020). Perturbations in glucose metabolism, epigenetics and mitochondria are all symptoms of AD (Cenini and Voos, 2019;Ehrlich, 2019;Esposito and Sherr, 2019). Notably, gastrulation establishes the platform upon which subsequent epigenetic determination of animal tissue-specific differentiated cell identity is based, and this may be related to changes in PGRMC1 function regulated by phosphorylation.…”
Section: The Role Of the S2r Complex Protein Pgrmc1 In Health And Patmentioning
confidence: 99%
“…Results reported by Dr. Cahill at the symposium have since been published (Thejer, Adhikary, Kaur, et al, 2020;Thejer, Adhikary, Teakel, et al, 2020). Perturbations in glucose metabolism, epigenetics and mitochondria are all symptoms of AD (Cenini and Voos, 2019;Ehrlich, 2019;Esposito and Sherr, 2019). Notably, gastrulation establishes the platform upon which subsequent epigenetic determination of animal tissue-specific differentiated cell identity is based, and this may be related to changes in PGRMC1 function regulated by phosphorylation.…”
Section: The Role Of the S2r Complex Protein Pgrmc1 In Health And Patmentioning
confidence: 99%
“…These patterns of synchronization ultimately guide developmental pathways during embryogenesis. Although aberrations in posttranslational modifications are often associated with developmental diseases including tumorigenesis [ 4 , 5 , 6 , 7 , 8 ], posttranslational events can also be manipulated and/or targeted for positive clinical applications [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the epigenetic alterations found in AD, DNA methylation and histone modifications show evident deregulation. It has been demonstrated that in AD brains changes in DNA methylation affect to a few common gene loci which play an essential role in the formation of Aβ plaques (Lord and Cruchaga, 2014;Watson et al, 2016;Qazi et al, 2018;Armstrong et al, 2019;Esposito and Sherr, 2019;Prasad and Jho, 2019). Among them, of particular interest are the differences in methylation in different regions of the APP gene promoters in the brains of humans with AD and these changes have been associated with neuropathological markers of this disorder (Bradley-Whitman and Lovell, 2013).…”
Section: Dna Damage and Repairmentioning
confidence: 99%
“…Also, chromatin organizing proteins and epigenetic regulators are mislocated in AD, affecting chromatin architecture (Winick-Ng and Rylett, 2018). Finally, in AD, other epigenetic modifications such as alterations in chromatin remodelers, phosphorylation of histones have been found (Esposito and Sherr, 2019), and might be associated with senescence.…”
Section: Dna Damage and Repairmentioning
confidence: 99%